A meta-analysis of temporal changes of response in the placebo arm of surgical randomized controlled trials: an update - Wartolowska, KA; Gerry, S; Feakins, BG; Collins, GS; Cook, J; Judge, A; Carr, AJ (BioMed Central, 2017)
Background Temporal changes in the placebo arm of randomized controlled trials (RCTs) have not been thoroughly investigated, despite the fact that results of RCTs depend on the comparison between arms. Methods In this update of our earlier systematic review and meta-analysis, we set out to investigate the effect of assessment time and number of visits on the magnitude of change from baseline in the placebo arm of these trials. We used linear mixed-effects models to account for within-trial correlations. Results Across all 47 trials the magnitude of response in the placebo arm did not change with time (β = -0.0070, 95% CI -0.024, 0.010) or visit (β = -0.033, 95% CI -0.082, 0.017) and remained significantly different from baseline for at least 12 months or seven follow-up visits. Change in the placebo arm in trials with subjective outcomes was large (β0 = 0.68, 95% CI 0.53, 0.82) and relatively constant across time (β = -0.0042, 95% CI -0.024, 0.016) and visit (β = -0.029, 95% CI -0.089, 0.031), whereas in trials with objective outcomes the response was smaller (β0 = 0.28, 95% CI 0.11, 0.46) and diminished with time (β = -0.030, 95% CI -0.050, -0.010), but not with visit (β = -0.099, 95% CI -0.30, 0.11). For trials with assessed outcomes, there was no significant effect of time (β = -0.0071, 95% CI -0.026, 0.011) or visit (β = -0.032, 95% CI -0.33, 0.26); however, these results should be interpreted with caution due to the small number of studies, and high clinical heterogeneity between studies. In trials with pain as an outcome, the improvement was significant (β0 = 0.91, 95% CI 0.75, 1.07), but there was no effect of time (β = -0.013, 95% CI -0.06, 0.03) or visit (β = -0.045, 95% CI -0.16, 0.069), and pain ratings remained significantly different from baseline for 12 months or seven visits. Conclusions These results are consistent with our previous findings. In trials with subjective outcomes response in the placebo arm remains large and relatively constant for at least a year, which is interesting considering that this is an effect of a single application of an invasive procedure. The lack of effect of time and visit number on subjective outcomes raises further questions regarding whether the observed response is the result of placebo effect or the result of bias.